Continuous conversion of furfural to furfuryl alcohol by transfer hydrogenation catalyzed by copper deposited in a monolith reactor. Issue 2 (1st November 2022) - Li, Tiefu; Liu, Jiaming; Li, Zipeng; Zhang, Peng; Yao, Yunlong; Sun, Zhichao; Wang, Yao; Liu, Ying-Ya; Wang, Anjie
Abstract : A polymer monolith catalytic reactor, which is fabricated by anchoring –SO3 H groups on the surface of the fibers and by depositing Cu species, exhibits outstanding performance and high stability in continuous transfer hydrogenation of furfural. Abstract : A monolith reactor was fabricated by growing carbonaceous fibers in a copper tube (i.d. 2 mm) via copper-catalyzed acetylene polymerization. The fibers were oxidized with air to convert CC bonds to CO bonds and to improve hydrophilicity. –SO3 H groups were anchored on the surface by amination. Cu species were introduced by deposition and subsequent reduction. The resultant Cu/CF-SO3 H monolith reactor was used to continuously and selectively convert furfural to furfuryl alcohol. At 180 °C, the monolith catalytic reactor performed significantly and stably in a 500 h run, maintaining a 100% conversion with a >99% selectivity. Additionally, the monolith reactor also performed well in continuous transfer hydrogenation of other α, β-unsaturated compounds, including 5-hydroxymethyl-2-furaldehyde, benzaldehyde, and cyclohexanone.